A coating material for preventing PET film from degrading and a preparation method thereof

By preparing a crosslinked coating of vinylpyrrolidone/methyl acrylate/fluorine-containing ethylene copolymer and graphene nanosheets on the surface of the PET substrate, the problem of degradation of PET substrate in lithium batteries is solved, and the effect of improving the corrosion resistance of electrolytes in lithium batteries is achieved.

CN118931300BActive Publication Date: 2025-04-11江世勇

Patent Information

Application Number
CN202411014813.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2025-04-11
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

PET substrates are prone to degradation in lithium batteries, especially when exposed to electrolyte and catalyst lithium alkoxyl, resulting in a degradation in the performance of lithium batteries.

Method used

Vinylpyrrolidone/methyl acrylate/fluoroethylene copolymer is used as film forming substances, graphene nanosheets are used as fillers, and a three-dimensional network structure is formed by cross-linking. The graphene nanosheets are chemically connected to the polymer network to prepare anti-degradation coating materials.

Benefits of technology

Effectively prevent the lithium battery electrolyte and the catalyst lithium alkoxyl from contacting with the PET substrate, prevent the degradation of the PET substrate, and improve the electrolyte corrosion resistance and overall performance of the lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004965398190000101
    Figure BDA0004965398190000101
  • Figure BDA0004965398190000102
    Figure BDA0004965398190000102
Patent Text Reader

Abstract

The present invention relates to the technical field of modification of lithium battery current collector materials, and provides a coating material and a preparation method for preventing PET film degradation. The coating material is a film-forming substance made of vinyl pyrrolidone / methyl acrylate / fluorinated ethylene copolymer and a graphene nanosheet as a filler. The main component of the film-forming substance is a polyvinyl pyrrolidone segment, and the relative content of the methyl acrylate segment and the fluorinated ethylene segment is small. In addition, the vinyl pyrrolidone / methyl acrylate / fluorinated ethylene copolymer forms a three-dimensional network structure through cross-linking, and the graphene nanosheet forms a chemical connection with the polymer network through a surface active group. The coating can effectively prevent the lithium battery electrolyte and the catalyst alkoxy lithium from contacting with the PET substrate, thereby preventing the PET substrate from degrading.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium battery current collector material modification, and provides a coating material for preventing PET film from degradation and a preparation method thereof. Background Art

[0002] In lithium batteries, the current collector collects current and carries the positive and negative active materials. In the process of lithium ions moving between the positive and negative electrodes to achieve charging and discharging, the current collector collects and outputs the current by contacting the active materials, thereby realizing the conversion of chemical energy into electrical energy. The current collector generally exists in the form of foil. Traditional foil is made of pure metal. The positive and negative potentials of lithium batteries determine that aluminum foil is used for the positive electrode and copper foil is used for the negative electrode.

[0003] Reducing the weight of the current collector and reducing the cost is one direction for the development of composite current collectors. For the negative electrode current collector, the composite current collector (PET copper foil) with a "Cu-PET-Cu" sandwich structure has become a research hotspot. The "Cu-PET-Cu" composite current collector is made of PET (polyethylene terephthalate) film as the substrate, and a metal copper layer is plated on the upper and lower sides. Due to the low density of the PET layer, the purpose of weight reduction is achieved.

[0004] Although the PET substrate has good heat resistance and physical strength, it will degrade to a certain extent when it encounters electrolyte. In addition, the alkoxy lithium (such as lithium methoxide, lithium ethoxide, lithium glycol) in the negative electrode SEI film can also play a significant catalytic role in the degradation of PET. PET degradation will cause a significant reduction in the performance of lithium batteries. Even if a small amount of degradation occurs on the PET surface, it will cause fundamental damage to the PET copper foil.

[0005] We know that when copper is plated on the surface of the substrate, it is difficult to avoid microscopic defects in the coating, and the stretching during the current collector processing will further amplify the defects, allowing the electrolyte and catalyst alkoxy lithium to penetrate the metal layer and contact PET. Therefore, the research on the use of technical means to prevent the degradation of the PET substrate in PET copper foil is of great significance for the development and application of composite current collectors. Summary of the invention

[0006] In view of the above situation, the present invention proposes a coating material and a preparation method for preventing PET film from degrading. The prepared coating can effectively prevent lithium battery electrolyte and catalyst alkoxy lithium from contacting with PET substrate, thereby preventing the PET substrate from degrading.

[0007] To achieve the above purpose, the specific technical solution of the present invention is as follows:

[0008] First, the present invention provides a method for preparing a coating material for preventing PET film from being degraded, and the specific steps are as follows:

[0009] (1) dissolving an emulsifier in deionized water, adding 1 / 5 of an initiator, stirring continuously, dropping a mixed monomer consisting of N-vinyl pyrrolidone and methyl acrylate, and introducing a fluorinated vinyl monomer, reacting at 60-70° C., adding 1 / 5 of the initiator at regular intervals until the addition is complete, reacting for 8-10 hours, and cooling to room temperature to obtain a vinyl pyrrolidone / methyl acrylate / fluorinated vinyl copolymer emulsion;

[0010] (2) adding graphene oxide nanosheets to ethylene glycol and ultrasonically treating the nanosheets, then adding sodium acetate and ethylenediamine hydrochloride, mixing well, transferring the mixture to a high-pressure reactor, reacting the mixture at 190-210° C. for 4-8 hours, washing the mixture with ethanol and deionized water, and vacuum drying the mixture to obtain modified graphene nanosheets;

[0011] (3) The modified graphene nanosheets are added to acetic acid / deionized water and ultrasonically treated, and then added to a vinylpyrrolidone / methyl acrylate / fluorinated ethylene copolymer emulsion, and then ammonium cerium sulfate and glutaraldehyde are added, and stirred to form a uniform mixture, and a PET film is immersed in the mixture, and then the film is pulled out, reacted at 55-65° C. for 8-10 hours, and then vacuum dried to form an anti-degradation coating material on the surface of the PET film.

[0012] Preferably, the emulsifier is composed of sodium dodecylbenzene sulfonate and alkylphenol polyoxyethylene ether in a mass ratio of 1:1-3.

[0013] Preferably, the initiator is one of potassium persulfate, ammonium persulfate and sodium persulfate.

[0014] Preferably, the fluorine-containing vinyl monomer is one of tetrafluoroethylene, vinylidene fluoride and hexafluoropropylene.

[0015] Further preferably, in step (1), the dropping speed of the mixed monomer is 1-2 mL / min, the introduction speed of the fluorine-containing vinyl monomer is 0.3-0.5 mL / min, and the time interval for adding the initiator is 20-40 min.

[0016] Further preferably, in step (1), the dosage ratio of N-vinyl pyrrolidone, methyl acrylate, fluorinated vinyl monomer, initiator, emulsifier and deionized water is 0.65-0.75 mol: 0.15-0.25 mol: 0.05-0.15 mol: 0.3-0.4 g: 3-5 g: 100 mL.

[0017] Preferably, the graphene oxide nanosheets are single-layer or few-layer nanosheets with a sheet diameter of 50-300 nm.

[0018] Further preferably, in step (2), the usage ratio of graphene oxide nanosheets, sodium acetate, ethylenediamine hydrochloride and ethylene glycol is 2-4 g: 8-10 g: 5-15 g: 100 mL.

[0019] Preferably, in step (3), the pulling speed of the PET film is 50-100 mm / min.

[0020] Further preferably, in step (3), the usage ratio of modified graphene nanosheets, ammonium cerium sulfate, glutaraldehyde, acetic acid, deionized water, and copolymer emulsion is 1-2g:0.02-0.03g:5-10mL:5-10mL:20-40mL:100g.

[0021] Step (1) uses N-vinyl pyrrolidone, methyl acrylate, and fluorine-containing vinyl monomer as comonomers, sodium dodecylbenzene sulfonate and alkylphenol polyoxyethylene ether as composite emulsifiers, and persulfate as initiator to carry out emulsion polymerization to obtain a copolymer emulsion. It is known that graphene nanosheets have a two-dimensional lamellar structure, and the surface of graphene oxide contains active groups such as hydroxyl, carboxyl, and epoxy groups. Step (2) uses ethylenediamine hydrochloride to modify the graphene oxide nanosheets so that some of the oxygen-containing groups on its surface are converted into amino groups, which have better reaction activity. On this basis, step (3) disperses the modified graphene nanosheets in an acidic solution, mixes with vinyl pyrrolidone / methyl acrylate / fluorine-containing ethylene copolymer emulsion, uses ammonium cerium sulfate as an initiator, and uses glutaraldehyde as a cross-linking agent to prepare a mixture, and the mixture is attached to the surface of the PET film by dipping and pulling. Since aldehyde substances (such as formaldehyde and glutaraldehyde) can be connected with the active groups of polyvinyl pyrrolidone and the active groups on the surface of modified graphene, during the heating process, on the one hand, the cross-linking agent forms a bridge between the different segments of polyvinyl pyrrolidone itself, so that the copolymer forms a three-dimensional network structure; on the other hand, the cross-linking agent can also form a bridge between the polyvinyl pyrrolidone segment and the modified graphene nanosheets, so that the graphene nanosheets are distributed in the cross-linked network and form a chemical connection with the cross-linked network.

[0022] The present invention also provides a coating material for preventing PET film degradation prepared by the above preparation method. The coating material is a film-forming material of vinyl pyrrolidone / methyl acrylate / fluorinated ethylene copolymer and a filler of graphene nanosheets. The main component of the film-forming material is a polyvinyl pyrrolidone segment, and the relative content of the methyl acrylate segment and the fluorinated ethylene segment is small. In addition, the vinyl pyrrolidone / methyl acrylate / fluorinated ethylene copolymer forms a three-dimensional network structure through cross-linking, and the graphene nanosheets are chemically connected to the polymer network through surface active groups.

[0023] Although polyvinyl pyrrolidone has good dissolving power, the cross-linked polyvinyl pyrrolidone (i.e., cross-linked polyvinyl pyrrolidone) formed by cross-linking not only has significantly reduced dissolving power, but also has good resistance to strong acids and alkalis, and is thus resistant to electrolyte corrosion. In addition, graphene also has good corrosion resistance and is not corroded by acids, alkalis, oxidants, etc. Therefore, the present invention uses cross-linked polyvinyl pyrrolidone as the main film-forming substance and graphene as the filler, and the prepared coating has good corrosion resistance, and the coating will not be destroyed after contacting the electrolyte, and can prevent the PET substrate from directly contacting the electrolyte and the catalyst.

[0024] Furthermore, the present invention uses graphene nanosheets, and uses its surface active groups to form a chemical connection with the polymer network. The graphene nanosheet has a two-dimensional lamellar structure, and its lamellar structure can extend the penetration path of the electrolyte and the catalyst in the coating, hindering the two from passing through the pores of the coating and contacting the PET substrate, and playing a good physical shielding and protective role. After the graphene nanosheet forms a chemical connection with the polymer network, on the one hand, the overall cross-linking degree of the coating is improved, making the corrosion resistance of the coating stronger. On the other hand, the graphene nanosheet is located at the cross-linking point position and is not easily displaced, which is conducive to the nanosheet maintaining a uniformly dispersed state and preventing the agglomeration between the sheets to ensure that the physical barrier effect of the sheet structure is fully exerted.

[0025] Further, the present invention introduces methyl acrylate and fluorine-containing ethylene monomers into cross-linked polyvinyl pyrrolidone for copolymerization. Because in the molecular chain of PET substrate, monomer units are connected with ester groups, and the side groups of polymethyl acrylate also contain a large amount of ester groups, thus, the introduction of methyl acrylate segments is conducive to improving the interface compatibility between coating and PET substrate, improving the adhesion firmness of coating. In addition, the introduction of fluorine-containing ethylene segments can reduce the surface energy of coating, improve the hydrophobic and oleophobic ability of coating, thereby reduce the adhesion of electrolyte on the coating surface, this can also play a certain hindering role to electrolyte through coating, and has a positive significance for improving electrolyte corrosion resistance.

[0026] The present invention provides a coating material and a preparation method for preventing PET film from being degraded, and the beneficial effects thereof are:

[0027] First, the present invention uses cross-linked polyvinyl pyrrolidone as the main film-forming substance and graphene as the filler to prepare a coating of a PET substrate. Since both of them have good acid and alkali corrosion resistance, the obtained coating can resist electrolyte corrosion and prevent the PET substrate from direct contact with the electrolyte and the catalyst, thereby preventing the PET substrate from degradation.

[0028] Second, the two-dimensional lamellar structure of graphene nanosheets can provide good physical shielding and protection for the penetration of electrolytes and catalysts in the pores of the coating, and form chemical connections between the graphene nanosheets and the polymer network, which not only improves the overall cross-linking degree of the coating, but also prevents the agglomeration of the sheets and reduces the physical barrier effect.

[0029] Third, the introduction of methyl acrylate segments containing ester groups on the side groups is beneficial to improving the interfacial compatibility between the coating and the PET substrate and improving the adhesion firmness of the coating.

[0030] Fourth, by introducing fluorinated vinyl segments, the surface energy of the coating can be reduced, the hydrophobic and oleophobic capabilities of the coating can be improved, the adhesion of the electrolyte on the coating surface can be reduced, and the electrolyte can be further prevented from penetrating the coating.

[0031] As can be seen from the above, the present invention uses vinyl pyrrolidone / methyl acrylate / fluorinated ethylene copolymer as a film-forming material and graphene nanosheets as fillers. The copolymer forms a three-dimensional network structure through cross-linking, and the graphene nanosheets are chemically connected to the polymer network through surface active groups. The prepared coating can effectively prevent the lithium battery electrolyte and the catalyst alkoxy lithium from contacting the PET substrate, thereby preventing the PET substrate from degrading. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below through specific embodiments, but this should not be construed as limiting the scope of the present invention to the following examples. Without departing from the above-mentioned method concept of the present invention, various substitutions or changes made according to common technical knowledge and conventional means in the art should be included in the scope of the present invention.

[0033] Example 1

[0034] (1) dissolving an emulsifier (sodium dodecylbenzene sulfonate and octylphenol polyoxyethylene ether OP-10 in a mass ratio of 1:2) in deionized water, adding 1 / 5 potassium persulfate, stirring continuously, adding a mixed monomer consisting of N-vinyl pyrrolidone and methyl acrylate dropwise at 1 mL / min, introducing hexafluoropropylene at 0.3 mL / min, reacting under reflux at 60° C., adding 1 / 5 potassium persulfate every 20 minutes until the addition is complete, reacting for 10 hours, and cooling to room temperature to obtain a vinyl pyrrolidone / methyl acrylate / hexafluoropropylene copolymer emulsion;

[0035] (2) adding graphene oxide nanosheets to ethylene glycol and ultrasonically treating the nanosheets, then adding sodium acetate and ethylenediamine hydrochloride, mixing well, transferring the mixture to a high-pressure reactor, reacting the mixture at 200° C. for 6 h, washing the mixture with ethanol and deionized water, and vacuum drying the mixture to obtain modified graphene nanosheets;

[0036] (3) The modified graphene nanosheets are added to acetic acid / deionized water and ultrasonically treated, and then added to a vinylpyrrolidone / methyl acrylate / hexafluoropropylene copolymer emulsion, and then ammonium cerium sulfate and glutaraldehyde are added, and stirred to form a uniform mixture, and a PET film is immersed in the mixture, and then the film is pulled out at 80 mm / min, reacted at 55° C. for 10 hours, and then vacuum dried to form an anti-degradation coating material on the surface of the PET film.

[0037] In step (1), the dosage ratio of N-vinyl pyrrolidone, methyl acrylate, hexafluoropropylene, potassium persulfate, emulsifier and deionized water is 0.7 mol: 0.2 mol: 0.1 mol: 0.35 g: 4 g: 100 mL.

[0038] In step (2), the usage ratio of graphene oxide nanosheets, sodium acetate, ethylenediamine hydrochloride and ethylene glycol is 3g:9g:10g:100mL.

[0039] In step (3), the usage ratio of modified graphene nanosheets, ammonium cerium sulfate, glutaraldehyde, acetic acid, deionized water, and copolymer emulsion is 1 g: 0.025 g: 6 mL: 5 mL: 20 mL: 100 g.

[0040] Example 2

[0041] (1) dissolving an emulsifier (sodium dodecylbenzene sulfonate and octylphenol polyoxyethylene ether OP-10 in a mass ratio of 1:2) in deionized water, adding 1 / 5 potassium persulfate, stirring continuously, adding a mixed monomer consisting of N-vinyl pyrrolidone and methyl acrylate dropwise at 2 mL / min, introducing hexafluoropropylene at 0.5 mL / min, reacting under reflux at 70° C., adding 1 / 5 potassium persulfate every 40 minutes until the addition is complete, reacting for 8 hours, and cooling to room temperature to obtain a vinyl pyrrolidone / methyl acrylate / hexafluoropropylene copolymer emulsion;

[0042] (2) adding graphene oxide nanosheets to ethylene glycol and ultrasonically treating the nanosheets, then adding sodium acetate and ethylenediamine hydrochloride, mixing well, transferring the mixture to a high-pressure reactor, reacting the mixture at 200° C. for 6 h, washing the mixture with ethanol and deionized water, and vacuum drying the mixture to obtain modified graphene nanosheets;

[0043] (3) The modified graphene nanosheets are added to acetic acid / deionized water and ultrasonically treated, and then added to a vinylpyrrolidone / methyl acrylate / hexafluoropropylene copolymer emulsion, and then ammonium cerium sulfate and glutaraldehyde are added, and stirred to form a uniform mixture, and a PET film is immersed in the mixture, and then the film is pulled out at 80 mm / min, reacted at 65° C. for 8 h, and then vacuum dried to form an anti-degradation coating material on the surface of the PET film.

[0044] In step (1), the dosage ratio of N-vinyl pyrrolidone, methyl acrylate, hexafluoropropylene, potassium persulfate, emulsifier and deionized water is 0.7 mol: 0.2 mol: 0.1 mol: 0.35 g: 4 g: 100 mL.

[0045] In step (2), the usage ratio of graphene oxide nanosheets, sodium acetate, ethylenediamine hydrochloride and ethylene glycol is 3g:9g:10g:100mL.

[0046] In step (3), the usage ratio of modified graphene nanosheets, ammonium cerium sulfate, glutaraldehyde, acetic acid, deionized water, and copolymer emulsion is 1.5 g: 0.025 g: 7 mL: 7.5 mL: 30 mL: 100 g.

[0047] Example 3

[0048] (1) dissolving an emulsifier (sodium dodecylbenzene sulfonate and octylphenol polyoxyethylene ether OP-10 in a mass ratio of 1:2) in deionized water, adding 1 / 5 potassium persulfate, stirring continuously, adding a mixed monomer consisting of N-vinyl pyrrolidone and methyl acrylate dropwise at 1.5 mL / min, introducing hexafluoropropylene at 0.4 mL / min, reacting under reflux at 65° C., adding 1 / 5 potassium persulfate every 30 minutes until the addition is complete, reacting for 9 hours, cooling to room temperature, and obtaining a vinyl pyrrolidone / methyl acrylate / hexafluoropropylene copolymer emulsion;

[0049] (2) adding graphene oxide nanosheets to ethylene glycol and ultrasonically treating the nanosheets, then adding sodium acetate and ethylenediamine hydrochloride, mixing well, transferring the mixture to a high-pressure reactor, reacting the mixture at 200° C. for 6 h, washing the mixture with ethanol and deionized water, and vacuum drying the mixture to obtain modified graphene nanosheets;

[0050] (3) The modified graphene nanosheets are added to acetic acid / deionized water and ultrasonically treated, and then added to a vinylpyrrolidone / methyl acrylate / hexafluoropropylene copolymer emulsion, and then ammonium cerium sulfate and glutaraldehyde are added, and stirred to form a uniform mixture, and a PET film is immersed in the mixture, and then the film is pulled out at 80 mm / min, reacted at 60° C. for 9 h, and then vacuum dried to form an anti-degradation coating material on the surface of the PET film.

[0051] In step (1), the dosage ratio of N-vinyl pyrrolidone, methyl acrylate, hexafluoropropylene, potassium persulfate, emulsifier and deionized water is 0.7 mol: 0.2 mol: 0.1 mol: 0.35 g: 4 g: 100 mL.

[0052] In step (2), the usage ratio of graphene oxide nanosheets, sodium acetate, ethylenediamine hydrochloride and ethylene glycol is 3g:9g:10g:100mL.

[0053] In step (3), the usage ratio of modified graphene nanosheets, ammonium cerium sulfate, glutaraldehyde, acetic acid, deionized water, and copolymer emulsion is 2g:0.025g:8mL:10mL:40mL:100g.

[0054] Comparative Example 1

[0055] Instead of using graphene oxide nanosheets, the coating was prepared using only vinyl pyrrolidone / methyl acrylate / hexafluoropropylene copolymer emulsion, and the other preparation processes and techniques were consistent with those in Example 3.

[0056] Comparative Example 2

[0057] Reduced graphene nanosheets are mixed with the copolymer latex, and the nanosheets are not modified, so there are no active groups on their surfaces. Other preparation processes and techniques are consistent with those in Example 3.

[0058] Comparative Example 3

[0059] In step (1), methyl acrylate was not added, and the dosage ratio of N-vinyl pyrrolidone, hexafluoropropylene, potassium persulfate, emulsifier and deionized water was 0.9 mol: 0.1 mol: 0.35 g: 4 g: 100 mL. The other preparation processes and techniques were consistent with those in Example 3.

[0060] Comparative Example 4

[0061] In step (1), hexafluoropropylene is not introduced, and the dosage ratio of N-vinyl pyrrolidone, methyl acrylate, potassium persulfate, emulsifier and deionized water is 0.8 mol: 0.2 mol: 0.35 g: 4 g: 100 mL. The other preparation process and technology are consistent with Example 3.

[0062] In the above examples and comparative examples, the graphene oxide nanosheets and reduced graphene nanosheets used were both single-layer nanosheets with a sheet diameter of 200±20 nm, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. The PET film used was purchased from Dongguan Jingtong Film Co., Ltd. and was pre-cut into a base film with a size of 10 cm×10 cm.

[0063] Assemble CR2025 button half-cells, where the electrolyte is fluoroethylene carbonate / dimethyl carbonate / ethylene carbonate (volume ratio of 1:2:2) containing 1 mol / LLiPF6, the separator is Celgard 2400 polypropylene microporous membrane, the positive electrode is lithium iron phosphate, and the negative electrode is a lithium sheet. Cycle charge and discharge 200 times at 2-5 V, 2C, then disassemble the battery and take out the electrolyte; add lithium methoxide (catalyst) to the electrolyte and stir evenly to prepare a treatment solution, where the mass ratio of lithium methoxide to electrolyte is 1:20.

[0064] (1) Take the PET films with coatings on the surface prepared in Examples 1-3 and Comparative Examples 1-4 respectively, and the test mass is M1; immerse the films in the treatment solution, heat to 50° C., stand for 24 hours, take out, wash with ether, and vacuum dry, and the test mass is M2; calculate the electrolyte corrosion resistance rate A1 of each PET film according to (M2 / M1)×100%;

[0065] (2) The PET film after vacuum drying in (1) is immersed in the treatment solution again, heated to 50° C., taken out after standing for 24 hours, washed with ether, and vacuum dried. The test mass is M3; the electrolyte corrosion resistance rate A2 of each PET film is calculated according to (M3 / M2)×100%;

[0066] (3) Take the PET films with coatings on the surface prepared in Examples 1-3 and Comparative Examples 1-4 respectively, and the test mass is m1; immerse the films in the treatment solution, heat to 50° C., stir at a high speed of 2000 rpm, and perform ultrasonic oscillation (ultrasonic frequency is 40 kHz) at the same time, take out after 24 hours, wash with ether, and vacuum dry, and the test mass is m2; calculate the electrolyte corrosion resistance B1 of each PET film according to (m2 / m1)×100%;

[0067] (4) The PET film after vacuum drying in (3) is immersed in the treatment solution again, heated to 50°C, taken out after standing for 24 hours, washed with ether, and vacuum dried. The test mass is m3; the electrolyte corrosion resistance B2 of each PET film is calculated according to (m3 / m2)×100%.

[0068] The results of the above tests are shown in Table 1. As can be seen from Table 1:

[0069] First, Examples 1-3 have good electrolyte corrosion resistance, and as the amount of modified graphene nanosheets added increases, the corrosion resistance becomes better and better; under high-speed stirring and ultrasonic oscillation conditions, the electrolyte corrosion resistance rate does not change significantly, indicating that the coatings of Examples 1-3 have good adhesion;

[0070] Second, compared with Example 3, the electrolyte corrosion resistance of Comparative Example 1 is significantly reduced. This is because Comparative Example 1 does not add graphene nanosheets, which cannot exert the excellent corrosion resistance of graphene and the physical barrier effect of the sheet structure, and the overall cross-linking degree of the coating is reduced; under high-speed stirring and ultrasonic oscillation conditions, the electrolyte corrosion resistance rate does not change significantly, indicating that the coating of Comparative Example 1 also has good adhesion;

[0071] Third, compared with Example 3, the electrolyte corrosion resistance of Comparative Example 2 is reduced to a certain extent. This is because Comparative Example 2 uses reduced graphene nanosheets, which have no active groups on the surface and cannot form a chemical connection with the polymer network, which reduces the overall crosslinking degree of the coating, and the nanosheets have a certain tendency to agglomerate and reduce their physical barrier effect; under high-speed stirring and ultrasonic oscillation conditions, the electrolyte corrosion resistance rate does not change significantly, indicating that the coating of Comparative Example 2 also has good adhesion;

[0072] Fourth, compared with Example 3, the electrolyte corrosion resistance of Comparative Example 3 is slightly improved. This is because the copolymer of Comparative Example 3 does not contain methyl acrylate segments, and the proportion of polyvinyl pyrrolidone segments is increased accordingly. However, after high-speed stirring and ultrasonic oscillation treatment, the electrolyte corrosion resistance of Comparative Example 3 is significantly reduced. This is because the copolymer of Comparative Example 3 does not contain methyl acrylate segments, and the interface bonding between the coating and the PET substrate is deteriorated. During the above treatment process, a small area of ​​the coating partly falls off, resulting in the electrolyte and the catalyst being able to pass through the coating and contact the PET substrate. It should be noted that the B1 value of Comparative Example 3 is significantly lower than the B2 value. This is because, compared with (4), high-speed stirring and ultrasonic oscillation were performed during the test of (3). Acoustic oscillation, the mass loss caused by local shedding of the coating is greater, that is, the difference between m1 and m2 (m1-m2) includes not only the mass loss caused by degradation of the PET film, but also the mass loss caused by local shedding of the coating. Therefore, the difference between m1 and m2 will be greater than the difference between m2 and m3 (m2-m3 is only the mass loss caused by degradation of the PET film). In addition, the B2 value of comparative example 3 is significantly lower than the A2 value. This is because, although high-speed stirring and ultrasonic oscillation are not performed during the test of (4), since (4) is continued to test the PET film after vacuum drying in (3), the coating has already partially shed during the process of (3), so the electrolyte and the catalyst can pass through the coating and contact the PET substrate during the process of (4).

[0073] Fifth, compared with Example 3, the electrolyte corrosion resistance of Comparative Example 4 is reduced to a certain extent. This is because there is no hexafluoropropylene segment in the copolymer of Comparative Example 4, the hydrophobic and oleophobic ability of the coating is reduced, and the electrolyte is more easily adhered to the surface of the coating and penetrates the coating; under high-speed stirring and ultrasonic oscillation conditions, the electrolyte corrosion resistance rate does not change significantly, indicating that the coating of Comparative Example 2 also has good adhesion.

[0074] By converting the electrolyte corrosion resistance rate (A1, A2, B1, B2) into the electrolyte corrosion rate (corresponding to A1', A2', B1', B2'), the difference in corrosion resistance between the above-mentioned embodiment and the comparative example can be more clearly seen. The converted electrolyte corrosion rate is shown in Table 2.

[0075] Table 1:

[0076]

[0077] Table 2:

[0078]

Claims

1. A method for preparing a coating material for preventing PET film from degrading, characterized in that: The specific steps are as follows: (1) dissolving an emulsifier in deionized water, adding 1 / 5 of an initiator, stirring continuously, dropping a mixed monomer consisting of N-vinyl pyrrolidone and methyl acrylate, and introducing a fluorinated vinyl monomer, reacting at 60-70° C., adding 1 / 5 of the initiator at regular intervals until the addition is complete, reacting for 8-10 hours, and cooling to room temperature to obtain a vinyl pyrrolidone / methyl acrylate / fluorinated vinyl copolymer emulsion; (2) adding graphene oxide nanosheets to ethylene glycol and ultrasonically treating the nanosheets, then adding sodium acetate and ethylenediamine hydrochloride, mixing well, transferring the mixture to a high-pressure reactor, reacting the mixture at 190-210° C. for 4-8 hours, washing the mixture with ethanol and deionized water, and vacuum drying the mixture to obtain modified graphene nanosheets; (3) The modified graphene nanosheets are added to acetic acid / deionized water and ultrasonically treated, and then added to a vinylpyrrolidone / methyl acrylate / fluorinated ethylene copolymer emulsion, and then ammonium cerium sulfate and glutaraldehyde are added, and stirred to form a uniform mixture, and a PET film is immersed in the mixture, and then the film is pulled out, reacted at 55-65° C. for 8-10 hours, and then vacuum dried to form an anti-degradation coating material on the surface of the PET film.

2. The method for preparing a coating material for preventing PET film from degrading according to claim 1, characterized in that: In step (1), the emulsifier is composed of sodium dodecylbenzene sulfonate and alkylphenol polyoxyethylene ether in a mass ratio of 1:1-3; the initiator is one of potassium persulfate, ammonium persulfate, and sodium persulfate; and the fluorine-containing vinyl monomer is one of tetrafluoroethylene, vinylidene fluoride, and hexafluoropropylene.

3. The method for preparing a coating material for preventing PET film from degrading according to claim 1, characterized in that: In step (1), the dropping speed of the mixed monomer is 1-2 mL / min, the introduction speed of the fluorine-containing vinyl monomer is 0.3-0.5 mL / min, and the time interval for adding the initiator is 20-40 min.

4. The method for preparing a coating material for preventing PET film from degrading according to claim 1, characterized in that: In step (1), the dosage ratio of N-vinyl pyrrolidone, methyl acrylate, fluorinated vinyl monomer, initiator, emulsifier and deionized water is 0.65-0.75 mol: 0.15-0.25 mol: 0.05-0.15 mol: 0.3-0.4 g: 3-5 g: 100 mL.

5. The method for preparing a coating material for preventing PET film from being degraded according to claim 1, characterized in that: In step (2), the graphene oxide nanosheets are single-layer or few-layer nanosheets with a sheet diameter of 50-300 nm.

6. The method for preparing a coating material for preventing PET film from being degraded according to claim 1, characterized in that: In step (2), the usage ratio of graphene oxide nanosheets, sodium acetate, ethylenediamine hydrochloride and ethylene glycol is 2-4 g: 8-10 g: 5-15 g: 100 mL.

7. The method for preparing a coating material for preventing PET film from being degraded according to claim 1, characterized in that: In step (3), the pulling speed of the PET film is 50-100 mm / min.

8. The method for preparing a coating material for preventing PET film from being degraded according to claim 1, characterized in that: In step (3), the usage ratio of modified graphene nanosheets, ammonium cerium sulfate, glutaraldehyde, acetic acid, deionized water, and copolymer emulsion is 1-2g: 0.02-0.03g: 5-10mL: 5-10mL: 20-40mL: 100g.

9. A coating material for preventing PET film from degrading obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Coating material for lithium ion battery diaphragm

    CN103408975A

  • Anticorrosive coating material with physically stripped graphene and method for preparing anticorrosive coating material

    CN105969025A

Cited By

  • Dynamic self-repairing degradation-resistant composite current collector BOPET film and preparation method thereof

    CN120757831A

  • Dynamic self-healing degradation-resistant composite current collector bopet film and method of making

    CN120757831B